EMPLOYEE TRAINING EFFECTIVENESS AND ORGANIZATIONAL PERFORMANCE IN INDONESIAN SERVICE COMPANIES - Endang Ruchiyat; Acu Kusnadar; Nia Riana (PT. Kreatif Indonesia Satu, 2024)
Background: Employee training investments constitute significant organizational expense requiring demonstrated returns through improved performance. Aims: This study examines relationships between employee training effectiveness and organizational performance in Indonesian service sector. Research Method: Survey of 189 service companies across hospitality, consulting, healthcare, and financial services combined with performance data analysis. Results and Conclusion: Effective training programs correlate with 34 percent higher employee productivity, 28 percent improved customer satisfaction, and 41 percent reduced turnover. Training effectiveness depends on needs assessment quality, content relevance, delivery methods, and post-training support. However, only 42 percent of companies conduct systematic training evaluation. Contribution: Research provides framework for Indonesian service organizations to design, implement, and evaluate training programs maximizing performance impacts while optimizing training investments.